The performance of Logit Model versus Altman's Z-score model in predicting bankruptcy of large industrial product firms in Malaysia / Asmahani Nayan and Abd Razak Ahmad - Nayan, Asmahani; Ahmad, Abd Razak (2014)
Most studies on bankruptcy prediction try to classify bankrupt firms from a pool of firms using financial ratios, macroeconomic variables and firms' nonfinancial information. As the financial and non-financial information are mostly collected from the financial statements, published at the end of the financial years, the information will be obsolete by the time they are being used to measure the financial health of firms. To overcome this problem we propose a hybrid model to include information taken from the stock market price information (SMPI) of the firms to estimate the probability of firms' failure. The aim of the work is to conclude why SMPI is or is not a good contributor to the model and to determine how efficient is the proposed model compared to the z-score model used by commercial banks.